2015
DOI: 10.1177/1468798414566705
|View full text |Cite
|
Sign up to set email alerts
|

“Okay, I will say in Korean and then in American”: Translanguaging practices in bilingual homes

Abstract: Building on the research on translanguaging practices in classrooms (e.g. García, 2009;Sayer, 2011) and immigrant families' literacy practices (e.g. Gregory et al., 2004;Li, 2006), this qualitative study explores the nature of translanguaging practices of four Korean bilingual children and their families in home literacy events. Participant observation with video recordings and field notes was used to gather data, and the data analysis focused on the literacy events defined by Heath (1982) and types of languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 45 publications
3
35
1
Order By: Relevance
“…The Translanguaging Classroom: Leveraging Student Bilingualism for Learning , one of the first books about translanguaging for teachers, provides practical guidelines about incorporating translanguaging in the classroom. Translanguaging, recently popularized by Ofelia García and other scholars in the field of bilingual education (Canagarajah, ; García & Wei, ; Otheguy, García, & Reid, ; Sayer, ; Song, ), refers to “the deployment of a speaker's full linguistic repertoire without regard for watchful adherence to the socially and politically defined boundaries of named (and usually national and the state) language” (Otheguy et al., , p. 283). Recognizing the deep‐seated monolingual ideology and a pervasive deficit orientation toward multilingual students in U.S. schools (García & Wei, ; Olsen, ; Valdés, ), the authors emphasize that “taking a translanguaging stance means viewing students’ dynamic bilingualism as an advantage, rather than as a problem to be solved” (García, Johnson, & Seltzer, , p. 118).…”
mentioning
confidence: 99%
“…The Translanguaging Classroom: Leveraging Student Bilingualism for Learning , one of the first books about translanguaging for teachers, provides practical guidelines about incorporating translanguaging in the classroom. Translanguaging, recently popularized by Ofelia García and other scholars in the field of bilingual education (Canagarajah, ; García & Wei, ; Otheguy, García, & Reid, ; Sayer, ; Song, ), refers to “the deployment of a speaker's full linguistic repertoire without regard for watchful adherence to the socially and politically defined boundaries of named (and usually national and the state) language” (Otheguy et al., , p. 283). Recognizing the deep‐seated monolingual ideology and a pervasive deficit orientation toward multilingual students in U.S. schools (García & Wei, ; Olsen, ; Valdés, ), the authors emphasize that “taking a translanguaging stance means viewing students’ dynamic bilingualism as an advantage, rather than as a problem to be solved” (García, Johnson, & Seltzer, , p. 118).…”
mentioning
confidence: 99%
“…For example, she feels that having two languages helps one get ahead, learn more, and is good when seeking employment. Similar to families in the literature, Emma feels it is important to maintain her children maintain their heritage language (Song, 2016;Valdés, 2001). She contrasted this with her sister's kids who live in another city and who seldom have any need to speak Spanish, except when family gets together.…”
Section: Rq3: Speech Patterns and Language Ideologies (Huerta)mentioning
confidence: 76%
“…Emma reported that she felt that Spanish allowed her to be sterner, where the kids would know that she was not joking around. This indicates that she had purposes for using certain languages in certain situations (Song, 2016), and those decisions reflected the beliefs she held about what those languages conveyed. Table 14) consists of Ana, her husband Pedro, Sr., and their three children: Pedro, Jr., Sarai (17), and Daniela (10).…”
Section: Rq3: Speech Patterns and Language Ideologies (Huerta)mentioning
confidence: 88%
See 2 more Smart Citations